Platelet hemostasis in patients with metabolic syndrome and type 2 diabetes mellitus: cGMP- and NO-dependent mechanisms in the insulin-mediated platelet aggregation - Suslova, Tatiana E.; Sitozhevskii, Alexei V.; Ogurkova, Oksana N.; Kravchenko, Elena S.; Kologrivova, Irina V.; Anfinogenova, Yana; Karpov, Rostislav S. (Frontiers in Physiology, 2015)
Patients with metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM) have high risk of microcirculation complications and microangiopathies. An increase in thrombogenic risk is associated with platelet hyperaggregation, hypercoagulation, and hyperfibrinolysis. Factors leading to platelet activation in MetS and T2DM comprise insulin resistance, hyperglycemia, non-enzymatic glycosylation, oxidative stress, and inflammation. This review discusses the role of nitric oxide (NO) in the regulation of platelet adhesion and aggregation processes. Nitric oxide is synthesized both in endotheliocytes, smooth muscle cells, macrophages, and platelets. Modification of platelet NO-synthase (NOS) activity in MetS patients can play a central role in the manifestation of platelet hyperactivation. Metabolic changes, accompanying T2DM, can lead to an abnormal NOS expression and activity in platelets. Hyperhomocysteinemia, often accompanying T2DM, is a risk factor for cardiovascular accidents. Homocysteine can reduce NO production by platelets. This review provides data on the insulin effects in platelets. Decrease in a number and sensitivity of the insulin receptors on platelets in T2DM can cause platelet hyperactivation. Various intracellular mechanisms of anti-aggregating insulin effects are discussed. Anti-aggregating effects of insulin are mediated by a NO-induced elevation of cGMP and upregulation of cAMP- and cGMP-dependent pathways. The review presents data suggesting an ability of platelets to synthesize humoral factors stimulating thrombogenesis and inflammation. Proinflammatory cytokines are considered as markers of T2DM and cardiovascular complications and are involved in the development of dyslipidemia and insulin resistance. The article provides an evaluation of NO-mediated signaling pathway in the effects of cytokines on platelet aggregation. The effects of the proinflammatory cytokines on functional activity of platelets are demonstrated.